2015
DOI: 10.3390/w7105203
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Transport Trajectory and Residence Time in Large River–Lake Systems: Application to Poyang Lake (China) Using a Combined Model Approach

Abstract: Abstract:The biochemical processes and associated water quality in many lakes mainly depend on their transport behaviors. Most existing methodologies for investigating transport behaviors are based on physically based numerical models. The pollutant transport trajectory and residence time of Poyang Lake are thought to have important implications for the steadily deteriorating water quality and the associated rapid environmental changes during the flood period. This study used a hydrodynamic model (MIKE 21) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…It can also examine the water residence and travel time of Tieshangang Bay. The MIKE 21 model has already been successfully applied in exploring different water bodies, such as Poyang Lake (China) [21], Vistula Lagoon (Poland and Russia) [22], the Gulf of Kachchh (India) [23], Alberni Inlet (Canada) [24], and Chilika Lagoon (India) [25]. Hence, we only give a brief description of the model here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also examine the water residence and travel time of Tieshangang Bay. The MIKE 21 model has already been successfully applied in exploring different water bodies, such as Poyang Lake (China) [21], Vistula Lagoon (Poland and Russia) [22], the Gulf of Kachchh (India) [23], Alberni Inlet (Canada) [24], and Chilika Lagoon (India) [25]. Hence, we only give a brief description of the model here.…”
Section: Methodsmentioning
confidence: 99%
“…We used the hydrodynamic module to obtain flow features of Tieshangang Bay. The particle tracking module was applied to track the spatial distributions of water particles, and thus to provide the transport trajectory using the Lagrangian random-walk technique [20,21]. It can also examine the water residence and travel time of Tieshangang Bay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrodynamic model in the MIKE21 FM is based on a flexible mesh approach. This model has been developed for applications within rivers, lakes, and coastal estuarine environments in China, such as Poyang Lake [39], Xiangjiang River [40], and Tieshan Bay [41]. The model is based on the solution of the incompressible Reynolds Averaged Navier-Stokes equations, which are subject to the assumptions of Boussinesq and hydrostatic pressure [42].…”
Section: ∂H ∂Tmentioning
confidence: 99%
“…Zhang et al (2011) explored water pollution incidents using a spatio-temporal simulation system, based on system dynamic and geographic information systems (GIS) models applied to the Songhua River, China [2]. In addition to the aforementioned studies, water quality models also have the potential to be applied in the study of water pollution incidents [8,9]. In particular, Cox (2003) reviewed a number of water quality models, especially QUAL2E (The Enhanced Stream Water Quality Model), MIKE-11, SIMCAT (SIMulation of CATchments), TOMCAT, ISIS, and QUASAR (Quality simulation along river systems), for estimating dissolved oxygen (DO) transportation in lowland rivers, and concluded that a model of medium complexity might be applicable for examining water quality issues [6].…”
Section: Introductionmentioning
confidence: 99%